(1340) the government role in development of the new industry countries-the case of Brazil and implications to Egypt دور الحكومة في تطوير الدول الصناعية الجديدة - حالة البرازيل وتداعياتها على مصر - tourk, khairy A. (The Institute Of National Planning., 2018)
Most developing nations suffer from balance of payments deficits and low rates of income growth.. Achieving simultaneous growth in income as well as improvement in the foreign sector represents one of the most difficult and challenging tasks facing developing countries. In general, most nations tend to have balance of payment difficulties during their initial stages of development as they tend to be importers of foreign resources' during that period (young debtor). Once the country develops